Policy Inclusiveness in Guaranteeing the Voting Rights of Persons With Disabilities: A Social Inclusion Study of the 2024 General Election in Palopo City - Ulfa Ulfa; Haliyah Haliyah (Department of Public Administration, 2025)
This study analyzes inclusion policies that ensure the political rights of persons with disabilities, using a Palopo City case study. It uses qualitative research and a case study approach to examine policy implementation from a social inclusion perspective. Data were collected from November 2024 to May 2025 using observation, interviews, and documentation. Informants included election organizers, disability communities, and voters with various disabilities in Palopo City, selected through purposive sampling for their relevance and experience with inclusion policies. The results show that inclusive election policies have been formally adopted. However, there are specific implementation gaps. These include limited physical access to polling stations, incomplete outreach and education for voters with visual and hearing impairments, and restricted involvement of disability communities. Their involvement is limited to just the socialization stage, with no role in planning or evaluation. These findings reinforce social inclusion theory. They underscore the need for a multidimensional approach that covers participation and relationships. This study strongly recommends strengthening synergy among policies, institutions, and the social environment. Effective cross-sectoral coordination among the General Election Commission, local government, and organizations of persons with disabilities is crucial for inclusive elections. This research advances inclusion theory and participatory policy. It highlights the critical importance of a multidimensional approach to creating inclusive, equitable policies.